Creative reconstruction: a structured literature review of the early empirical research on the COVID-19 crisis and entrepreneurship - Andreas Kuckertz; Leif Brändle (Management Review Quarterly, 2021)
The COVID-19 crisis triggered by the novel coronavirus (SARS-CoV-2) and the infection control measures taken have extended beyond affecting health issues to impact economic activity worldwide. In this structured literature review, the focus is specifically on how the crisis has impacted entrepreneurial activity. The review focuses on the early empirical literature that primarily relied on data collected during the first wave of the pandemic. These empirical results are synthesized in a thematic literature review. The entrepreneurship research on the COVID-19 crisis is marked by three perspectives: the uncertainty perspective, the resilience perspective, and the opportunity perspective. To obtain a complete picture of the effects of the crisis on entrepreneurship, these three perspectives should be considered in combination. We provide implications for future research, policymakers, and entrepreneurs discussing how the interplay of the reviewed perspectives provides paths toward creative reconstruction, that is, the opportunity to move beyond pre-crisis levels of innovation and entrepreneurial action.
Keywords: L26; 650; COVID-19; SARS-CoV-2; Coronavirus; Entrepreneurship; Uncertainty; Opportunity; Resilience; Structured literature review